Halal Economy and Consumer Protection Laws: A Legal-Economic Perspective - Tofig Hasanov; Muhammad Rafi Thoriq; Sujoko Winanto; Nigar Aliyeva (Journal of Islamic Law and Legal Studies, 2026)
The rapid growth of the global halal economy has positioned halal products and services as important contributors to international trade, economic development, and evolving consumer markets. This study investigates the role of halal consumer protection law in supporting the advancement of the halal economy from both legal and economic perspectives. Employing a qualitative approach with a juridical normative framework, this research examines regulatory structures, halal certification mechanisms, consumer protection principles, and the broader economic implications of halal governance. The findings indicate that effective halal consumer protection frameworks are essential for establishing legal certainty, preserving product authenticity, strengthening consumer trust, and improving market transparency. From an economic perspective, comprehensive halal regulations contribute to enhancing product competitiveness, expanding global market access, encouraging industrial innovation, attracting investment, and promoting sustainable economic growth. Nevertheless, this study highlights several ongoing challenges, including the lack of harmonization among international halal standards, limited regulatory enforcement capacity, the financial burden of certification processes for micro, small, and medium enterprises (MSMEs), and the increasing complexity of digital trade and cross-border e-commerce.